OCCURRENCE OF GELOINA BENGALENSIS (LAMARCK) (GELOINIIDAE: EULAMELLIBRANCHIA) IN THE COLEROON ESTUARY - Natarajan, P (Indian Journal of Fisheries, 2011)
The occurrence of Geloina bengalensis (Lamarck) in Coleroon estuary, on the south-east coast of India, is reported, based on a few shells collected from the area